PENERAPAN INTEGRASI SISTEM ERP TERHADAP EFISIENSI PROSESPENGADAAN DENGAN PENDEKATAN TEKNIK INDUSTRI DI PT. GARUDA MAINTENANCE FACILTY AEROASIA TBK - RANGGA, MUHAMAD; INDRAMAWAN, INDRAMAWAN; MUHDHOR, FAHMA DIANA; BHIRAWA, WASPADA TEDJA; ARIANTO, BASUKI (JURNAL TEKNIK INDUSTRI, 2024)
In the MRO industry, supply chain and inventory management are crucial aspects thataffect a company’s operational performance. An efficient procurement process ensures the availability of required spare parts and materials without causing overstock or stockout, which can disrupt operations. The integration of ERP systems at GMF AeroAsia allows the company to have better visibility into their supply chain, manage inventory in real-time, and optimize procurement processes more effectively. Thus, the implementation of ERP systems becomes a key strategy in supporting the company’s operational efficiency and competitiveness goals in the global market.An industrial engineering approach is applied to evaluate and improve the efficiency of the procurement process through the integration of ERP systems. Industrial engineering provides various analysis methods such as workflow analysis, time and motion study, and cost-benefit analysis to understand and improve business processes. At GMF AeroAsia, this approach helps identify bottlenecks in the procurement process, reduce cycle time, and optimize resource utilization. The results of this implementation not only improve operational efficiency but also reduce costs and increase customer satisfaction.This report aims to evaluate the impact of ERP system implementation on the efficiency of the procurement process at GMF AeroAsia. The expected outcome is a deeper understanding of the benefits of ERP system integration and identification of areas that require further improvement. This report will provide practical recommendations for GMF AeroAsia and other companies in the MRO industry considering similar implementations. Thus, this report is not only relevant to GMFAeroAsia but also to the development of the MRO industry as a whole, supporting increased efficiency and competitiveness in the digital era.Keywords : Enterprise Resource Planning, Supply Chain Management, Material Requirements Planning, GMF AeroAsia.